Media Representation of Violent Teen Gangs: Effects on Non-Gang Youth (Social Science Review, 2026)
The recent growth in teen gangs has sparked the interest of people from all aspects of society, including politicians, academics, law enforcement organizations, and legislators. Primarily, juvenile gangs start with peer groups, but eventually are recognized as engaging in a variety of unlawful activities. This fact raises suspicion about the non-gang peer groups and their members in the same neighbourhood as being involved in those activities as well. While the media highlights teen gangs to comprehend the situation and gives us vital information, it does tend to present these youngsters horribly. When we focus on teen gangs, we disregard the non-gang members who coexist with them. As a result of the constant labelling they receive from the media, individuals are vulnerable to a range of difficulties. The purpose of this study is to identify the problems that these non-gang teenagers experience, as well as the qualities that predispose them to these problems, in light of Howard Becker’s labelling theory. The paper’s methodology is qualitative, and the method is a semi-structured interview. People’s viewpoints are influenced by their spatial surroundings, gender, and socioeconomic position. A few teens appeared to have encountered more serious problems than others. If these problems are not addressed, more teens might retaliate. Both parents and society need to come forward and healthily address these problems. Law enforcement groups can conduct seminars for teenagers to teach them about gangs and their destructive implications.Social Science Review [The Dhaka University Studies, Part-D], Vol. 42, No.2, December 2025, pp. 245-263